Legal impediments to procedural disagreement - ., Dr. Naba Mohammed Abed; ., Dr. Aqeel Majeed Taha (TIKRIT UNIVERSITY JOURNAL FOR RIGHTS, 2024)
Abstract: The death of the litigant during the course of the procedures achieves the succession in the procedures, when he attend. Thus, the heirs replace the predecessor in the face of the lawsuit procedures, and certainly the procedures are not repeated again, but rather from the stage in which the procedures were interrupted upon the death of the opponent, but there may be obstacles that prevent the succession from being realized in the procedures. When there is an impediment, the procedural succession is negated, and these impediments may be related to the right holder and obstacles related to the right itself. There is no clear criterion that determines the extent to which cases are transferred or not by succession in the Iraqi legislation. The litigation related to the estate of the deceased and the position of the judiciary, the jurisprudence of the Iraqi courts, especially the Federal Court of Cassation, approved principles and decisions Contrasting opinions regarding adding the case to the inheritance as a legal person independent of the heirs, or that the case is brought against the heirs in their personal capacity, given that the heir owns the money that was transferred to him from the inheritance upon death, and this in turn was reflected in the conflicting court rulings in this regard .